2017
DOI: 10.1038/lsa.2017.177
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet laser photolysis of hydrocarbons for nondiamond carbon suppression in chemical vapor deposition of diamond films

Abstract: In this work, we demonstrate that ultraviolet (UV) laser photolysis of hydrocarbon species alters the flame chemistry such that it promotes the diamond growth rate and film quality. Optical emission spectroscopy and laser-induced fluorescence demonstrate that direct UV laser irradiation of a diamond-forming combustion flame produces a large amount of reactive species that play critical roles in diamond growth, thereby leading to enhanced diamond growth. The diamond growth rate is more than doubled, and diamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…It demonstrated that the obtained graphene layer on DLC had comparable conductivity and transparency performances to those of ITO. In addition, Fan et al [ 53 ] used hydrocarbon species including a mixture of acetylene (C 2 H 2 ), ethylene (C 2 H 4 ) and oxygen (O 2 ) as the precursor, a combustion torch was used to produce the flames and an ultraviolet (UV) laser was used to excite the combustion species in the direction of perpendicular to the combustion flames and parallel to the substrate (Fig. 4 a, b).…”
Section: Laser As the Synthetic Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrated that the obtained graphene layer on DLC had comparable conductivity and transparency performances to those of ITO. In addition, Fan et al [ 53 ] used hydrocarbon species including a mixture of acetylene (C 2 H 2 ), ethylene (C 2 H 4 ) and oxygen (O 2 ) as the precursor, a combustion torch was used to produce the flames and an ultraviolet (UV) laser was used to excite the combustion species in the direction of perpendicular to the combustion flames and parallel to the substrate (Fig. 4 a, b).…”
Section: Laser As the Synthetic Techniquementioning
confidence: 99%
“…4 a Schematic diagram of the optical emission spectroscopy (OES) and laser-induced fluorescence (LIF) setup to characterize the species in the combustion flame with UV laser irradiation. b Schematic illustration of the UV-laser-assisted diamond combustion CVD setup [ 53 ] …”
Section: Laser As the Synthetic Techniquementioning
confidence: 99%
“…Nevertheless, laser chemical control studies have been focused on simple molecular reactions for a long time because of limited choices and high cost of laser sources. The increasing versatility of laser sources and their notably reduced operational cost make it possible to envision their enormous potential for enabling a control in practical applications (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…It is a popular method and technique for identification and analysis because it is nondestructive, requires no sample preparation, and both organic and inorganic substances can be measured in various states. Owing to these advantages, Raman spectroscopy has already been applied in a variety of fields, including physics, chemistry, biology, medicine, geology, and electronics . A spatial heterodyne Raman spectrometer (SHRS) possesses the multiple advantages, a larger entrance or higher light throughput than that a dispersion system, high spectral resolution, a compact, and rugged package without moving parts, and is compatible with a pulsed laser and gated detectors under ambient light conditions .…”
Section: Introductionmentioning
confidence: 99%